Facteurs Explicatifs Du Tarissement Des Points D’eau En Milieu De Socle Cristallin Dans Le Departement Des Collines Au Benin - Koumassi, Dègla Hervé (European Scientific Journal, ESJ, 2017)
The department of the hills is located at the center of Benin in plinth area. The water supply in this area is more and more directed towards surface water due to the hydrogeologic constraints and the impact of the climatic fluctuations. The climatological and geological data analysis made by the methods of descriptive statistical analysis made it possible to analyze the dynamics of the climatic parameters on the one hand and the behavior of the geological units to the recorded flows. The hydroclimatic study showed a deficit on the level of the climatic assessment and a decline of pluviometry since 1970. The study of the hydrogeologic characteristics carried out on 706 drillings made it possible to show the relationship between various parameters such as: thickness of change, flows end of boring and productivity of the drilling / lithology.